Pemanfaatan Data Analytics untuk Mengkaji Pengaruh Motivasi, Kepuasan Kerja, dan Lingkungan Terhadap Kinerja Karyawan di Glory Industrial Semarang - Rejeki, Sri; Sugianto, Efendi; Sugiharto, Bambang; Lassa, Anita; Liem, Jhon Sepron Defretus (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
This study employs data analytics to examine the influence of motivation, job satisfaction, and the work environment on employee performance at Glory Industrial Semarang. Using a quantitative approach, the study involved a population of 300 employees, with a sample selected through probability sampling using the simple random sampling technique, resulting in 78 respondents. Data analysis was conducted using SPSS, revealing that the variables of job satisfaction, motivation, and the work environment each have a positive and significant impact on employee performance. The job satisfaction variable has a regression coefficient of 0.293 with a significance of 0.024, the motivation variable has a coefficient of 0.349 with a significance of 0.002, and the work environment variable has a coefficient of 0.262 with a significance of 0.000. These findings confirm that data analytics is effective in identifying factors that contribute to the enhancement of employee performance within the company
Keywords: Data Analytics; Glory Industrial; Job Satisfaction; Performance; Environment; Motivation